Occult roots of religious studies : on the influence of non-hegemonic currents on academia around 1900 - Mühlematter, Yves; Zander, Helmut, 1957- (Berlin : De Gruyter Oldenbourg, 2021)
The historiographers of religious studies have written the history of this discipline primarily as a rationalization of ideological, most prominently theological and phenomenological ideas: first through the establishment of comparative, philological and sociological methods and secondly through the demand for intentional neutrality. This interpretation caused important roots in occult-esoteric traditions to be repressed.This process of "purification" (Latour) is not to be equated with the origin of the academic studies. De facto, the elimination of idealistic theories took time and only happened later. One example concerning the early entanglement is Tibetology, where many researchers and respected chair holders were influenced by theosophical ideas or were even members of the Theosophical Society. Similarly, the emergence of comparatistics cannot be understood without taking into account perennialist ideas of esoteric provenance, which hold that all religions have a common origin.In this perspective, it is not only the history of religious studies which must be revisited, but also the partial shaping of religious studies by these traditions, insofar as it saw itself as a counter-model to occult ideas.
The Occult Roots of Religious Studies: An Introduction / Yves Mühlematter, Helmut Zander -- What Is Esotericism? Does It Exist? How Can It Be Understood? / Helmut Zander -- The Science of Religion, Folklore Studies, and the Occult Field in Great Britain (1870-1914): Some Observations on Competition and Cain-Abel Conflicts / Marco Frenschkowski -- Magnetism, Spiritualism, and the Academy: The Case of Nees von Esenbeck, President of the Academy of the Natural Sciences Leopoldina (1818-1858) / Daniel Cyranka -- Academic Study of Kabbalah and Occultist Kabbalah / Boaz Huss -- Tantra as Experimental Science in the Works of John Woodroffe / Julian Strube -- A Common Core of Theosophy in Celtic Myth, Yoga, and Tibetan Buddhism: Walter Y. Evans-Wentz and the Comparative Study of Religion / Jens Schlieter -- Paul Masson-Oursel (1882-1956): Inside and Outside the Academy / Léo Bernard -- The Ancient Processional Street of Babylon at the Pergamonmuseum Berlin: Walter Andrae's Reconstruction and Its Anthroposophical Background / Sabine Böhme -- Short biographies -- Ayni, Mehmet Ali (1868-1945) / Dilek Sarmis -- Beckh, Hermann (1875-1937) / Helmut Zander -- Coomaraswamy, Ananda Kentish (1877-1947) / Mark Sedgwick -- Ehrenfels, Baron Omar (Umar) Rolf von (1901-1980) / Reinhard Schulze -- Faivre, Antoine (*1934) / Helmut Zander -- Johnston, Charles (1867-1931) / Yves Mühlematter -- Kamensky, Anna (1867-1952) (Anna Alexeyevna Kamenskaya) / Florence Pasche Guignard -- Helmut ZanderMead, George Robert Stow (1863-1933) 253Léo BernardMéautis, Georges (1890-1970) Rousselle, Erwin (1890-1949) / Karl Baier -- Schrader, Friedrich Otto (1876-1961) / Judith Bodendörfer -- Seidenstücker, Karl Bernhard (1876-1936) / Yves Mühlematter -- Suzuki, Daisetsu Teitarō (1870-1966) / Hans Martin Krämer -- Manen, Mari Albert Johan (1877-1943) / Karénina Kollmar-Paulenz.
Kuvailun perustana verkkoaineisto; nimeke PDF-nimiösivulta (De Gruyter, katsottu 25.11.2022).
Keywords: Occultism -- History -- 19th century; Occultism -- History -- 20th century; Occultism -- Religious aspects; Religion -- Study and teaching -- History -- 19th century; Religion -- Study and teaching -- History -- 20th century; okkultismi; esoterismi; tantra; teosofia; kabbala; antroposofia; uskontotiede; oppihistoria; ockultism; esoterism; tantra; teosofi; kabbala; antroposofi; religionsvetenskap; lärdomshistoria; Pergamonmuseum (Berlin, Germany); Nees von Esenbeck, Theodor Friedrich Ludwig, -- 1787-1837.; Woodroffe, John George, -- Sir, -- 1865-1936.; Evans-Wentz, W. Y. -- 1878-1965.; Masson-Oursel, Paul, -- 1882-1956.; Andrae, Walter, -- 1875-1956.; 1800-luku.; 1900-luku.; 1800-talet.; 1900-talet.